Measurement of the ratio of branching fractions B (B+c→J [psi] [tau] + [nu] [tau])/B(B+c→J/[psi] [mu] + [nu] [mu]) - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Berninghoff, Daniel; Braun, Svende; Comerma-Montells, Albert; De Cian, Michel; Dziewiecki, Michal; Gerick, David; Grabowski, Jascha; Grünberg, Oliver; Han, Xiaoxue; et al. (Physical review letters, 2018)
A measurement is reported of the ratio of branching fractions R(J/ψ)=B(B+c→J/ψτ+ντ)/B(B+c→J/ψμ+νμ), where the τ+ lepton is identified in the decay mode τ+→μ+νμ¯ντ. This analysis uses a sample of proton-proton collision data corresponding to 3.0 fb−1 of integrated luminosity recorded with the LHCb experiment at center-of-mass energies of 7 and 8 TeV. A signal is found for the decay B+c→J/ψτ+ντ at a significance of 3 standard deviations corrected for systematic uncertainty, and the ratio of the branching fractions is measured to be R(J/ψ)=0.71±0.17(stat)±0.18(syst). This result lies within 2 standard deviations above the range of central values currently predicted by the standard model.